Multiple solutions in dyads or alone – Fostering the acquisition of modeling competencies in mathematics. (December 2022) - Große, Cornelia S.
Abstract: Generating multiple solutions is a promising approach in order to foster deep insight and understanding in mathematical contexts. However, in complex domains, students often struggle to generate just one solution, let alone more than one. This study investigates whether collaboration supports learners to generate multiple solutions, and to what extent collaboration and generating multiple solutions foster the acquisition of modeling competencies. In an experiment, students either learned alone or in dyads which were homogeneous or heterogeneous with respect to the level of prior knowledge, and they were prompted to generate one or multiple solutions in the learning phase ( N = 193 seventh and eighth graders). Learning in homogeneous dyads fostered the acquisition of modeling competencies. Being prompted to generate a second solution was beneficial only for learners with high prior knowledge; overall, actually generating a second solution had positive impact. Highlights: Learners most successfully acquired mathematical competencies in homogeneous dyads. Prompting multiple solutions was effective only for high prior knowledge learners. Generating multiple solutions was beneficial. Collaboration may provide a fruitful basis for generating multiple solutions.